Analysis of the Phytochemistry and Bioactivity of the Genus Polygonum of Polygonaceae - Bing-Bing Shen; Yu-Pei Yang; Sumera Yasamin; Na Liang; Wei Su; Sheng-Huang Chen; Xiao-Juan Wang; Wei Wang (KeAi Communications Co., Ltd., 2018)
ABSTRACT: The main chemical constituents of the genus Polygonum (Polygonaceae) are flavonoids, quinones, phenylpropanoids, and terpenoids, which show anticancer, antitumor, anti-oxidative, anti-inflammatory, analgesic, antibacterial, insecticidal, and other pharmacological effects. This paper summarizes research on the chemical constituents and pharmacological effects of compounds from the genus Polygonum in last 15 years. Keywords: Polygonum, Chemical constituents, Bioactivity, Flavonoid, Anticancer